Fungsi Seni Lukis Bali Modern Anak Agung Gede Sobrat - A.A Gede Yugus (Mudra Jurnal Seni Budaya, 2007)
This article examines the important of appreciating the paintings of A.A. Gede Sobrat, due to the interesting form, theme, and function of the painting. The work of this painter has its distinctive characteristic that is well known and has enhanced the artistic level of Bali and Indonesia in painting. Anak Agung Gede Sobrat obtained inspiration from Walter Spies and R. Bonnet, although Sobrat previously focused on Balinese traditional painting. His encounter with Walter Spies and R. Bonnet provides artistic ideas in painting arts. The author wishes to understand the form, function, and meaning of the artistic exploration of Anak Agung Gede Sobrat.